Efektivitas Pengawasan Badan Penyelesaian Sengketa Konsumen pada Pencantuman Klausul Baku di Provinsi Dki Jakarta - Rizky Darmawan; Mustolih Mustolih (JOURNAL of LEGAL RESEARCH, 2020)
This thesis aims to determine the effectiveness of BPSK supervision on the inclusion of standard clauses in DKI Jakarta Province, and how the regulations related to the supervision of standard clauses are regulated in the Decree of the Minister of Industry and Trade No. 350 / MPP / Kep / 12/2001 regarding the implementation of duties and authorities of the Settlement Body. Consumer Disputes. The type of research used in this research is empirical juridical. Juridical empirical is an approach taken to analyze the extent to which a regulation or statute or law is currently in effect. The results of this thesis research indicate that the DKI Jakarta BPSK has not been able to play an active role in supervising the inclusion of standard clauses according to their duties and authorities because there are no regulations related to technical rules regarding standard clause supervision in the consumer protection law. Even though it has not been optimal in monitoring standard clauses, in this case the DKI Jakarta Provincial BPSK assemblies can only interpret their authority as stated in the consumer protection law regarding the supervision of the inclusion of standard clauses. Although it is still in the stage of groping and learning from cases that have been disputed by consumers in carrying out standard clause supervision.